Analisis Aspek-Aspek Yang Mempengaruhi Pembiayaan Modal Kerja di Bank Tabungan Negara KC Syariah Medan - Silvia Anggrie Nst; Nursantri Yanti (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Working capital products are one of the products offered and distributed by the State Savings Bank, Medan Sharia Branch Office, which is in great demand by customers because human needs are unlimited. This research uses qualitative research with the data used is secondary data, namely through literature study. The benefit of doing working capital financing at a bank is being able to finance the company's daily expenses or operations. With sufficient working capital, the company will operate economically and efficiently and not experience financial difficulties. The aspects of working capital financing at BTN Syariah are due to interest from customers and factors such as superior service, processing speed, competitive profit sharing ratio, as well as the availability of desired funds, margins, third party funds, and non-financing. performance financing which is an aspect of working capital financing at BTN Syariah KC Medan bank.